A modelling approach for predicting the initial phase of Egyptian broomrape (Phelipanche aegyptiaca) parasitism in potato. (October 2017) - Hosseini, Pershang; Ahmadvand, Goudarz; Oveisi, Mostafa; Morshedi, Parisa; Gonzalez-Andujar, Jose L.
Abstract: Phelipanche aegyptiaca is one of the most important parasitic weeds in some crops including potato. P.aegyptiaca reduces potato tuber size and can produce severe yield losses. The development of predictive models can be useful to help managers to choose the best management options and times and, thereby, improve weed control.The objective of this study was to develop a predictive thermal time model of the P.aegyptiaca establishment in potato using field experiment data. The relationship between the cumulative attachments of P.aegyptiaca and air/soil thermal time was analysed using Gompertz and Weibull functions. The Weibull soil thermal time model produced the better fit and was the more plausible one. The latter model was successfully validated under field conditions and can be used as a predictive tool contributing to optimize the timing of P.aegyptiaca control. According to the weibull model and soil thermal time the lag time and 50% of P.aegyptiaca attachments occurred in 613.75 (124.8) and 999.49 (5.98) TT respectively. Highlights: Tow equations used for predicting P.aegyptiaca attachments in potato based on thermal time model. Thermal time accounted with soil and air temperature. The 4 parameter weibull model with lag phase was the best model. A correcting coefficient can be used for turning air temperature to soil temperature. The predicting model can be used for P.aegyptiaca management.